Tindak Tutur Ilokusi Asertif dalam Channel YouTube Satu Persen bertema Strategi Meningkatkan Produktivitas - Helga Tsania Rahma Putri; Meca Chelsillia Ayunindar Putri; Herlina Novita Sari; Siti Anisa Priyanti; Syafina Izzatun Yazidahayu; Asep Purwo Yudi Utomo; Rossi Galih Kesuma (Universitas Palangka Raya, 2026)
This research explores assertive speech acts found on the Satu Persen YouTube Channel, particularly in the video titled “Strategies to Increase Productivity.” Assertive speech acts are considered significant as they serve to deliver information, clarification, and recommendations that can influence the audience’s perceptions and behaviors. The main objective of this study is to identify the forms of assertive speech acts that appear and explain their functions in reinforcing educational and motivational messages. This study employed a qualitative descriptive approach using observation and note-taking techniques. The data, taken from utterances in four purposively selected videos, were transcribed and categorized according to the types of assertive speech acts. The findings reveal a total of 194 assertive speech acts encompassing various forms, including stating, demanding, admitting, reporting, showing, mentioning, testifying, and speculating. Among these, the stating form appeared most frequently with 73 occurrences, followed by admitting, saying, and speculating. These results suggest that the creator focuses on delivering factual, logical, and structured information to facilitate audience comprehension. Overall, this study emphasizes the crucial role of assertive speech acts in conveying educational and motivational messages while demonstrating YouTube’s potential as an effective medium for academic communication and contributing to the advancement of pragmatic studies.